Patterns of invertebrate food availability and the persistence of an avian insectivore on the brink. (14th March 2019) - Stone, Zoë L.; Tasker, Elizabeth; Maron, Martine
Abstract: Globally, insectivorous birds are at high risk of decline. One explanation of this relates to changes in invertebrate resources due to anthropogenic pressures. The northern population of the eastern bristlebird ( Dasyornis brachypterus ) relies heavily on invertebrate food resources, and has experienced an 80% population reduction over the past 40 years. We investigated invertebrate abundance and nutritional quality across 23 currently and historically occupied northern bristlebird sites to determine whether extant territories were associated with more, or more nutritious, invertebrate resources. Pitfall and leaf‐litter invertebrate sampling were done in both breeding and non‐breeding seasons from 2014 to 2016. There was no difference in abundance, biomass or nutritional value of invertebrates between occupied and abandoned territories; however, within territories invertebrate abundance and nutritional value did correspond to the habitat characteristics with which bristlebirds are associated. Nutritional value of invertebrates increased with proximity to rainforest, while the abundance of macro‐invertebrates (>1 mm) was correlated with grass height. Bristlebird territories are often close to rainforest margins, and these ecotones may provide more nutritious mesic‐associated invertebrates. Higher abundances of large invertebrates in tall grasses may also contribute to the known association of bristlebirds with tall grasses. Maintenance of tall grass adjacent to rainforest through appropriate fire and grazing management is likely to be important for northern bristlebird recovery and long‐term persistence of the population.